The Influence of System Quality and Information Quality on Gojek Application User Satisfaction - Devie Amelia; Ifan Wicaksana Siregar (Profesional Muda Cendekia Publishing, 2023)
The quality of the system and the quality of information can influence user satisfaction with online transportation applications. This study aims to determine the influence of system quality and information quality on user satisfaction with the Gojek application among students at the Faculty of Economics and Business (FEB), Unjani. This research utilizes a quantitative survey method with a research instrument in the form of a questionnaire. The sample size consists of 100 active students from FEB, Unjani. The results of the statistical analysis indicate that the system quality variable produces a t-value < t-table and a Sig-value > α. On the other hand, the information quality variable produces a t-value > t-table and a Sig-value < α. The results of the F-test show that the calculated F-value is greater than the tabulated F-value, and the significance level (p-value) is 0.000 < 0.05. Thus, it can be concluded that partially, system quality does not have an influence on user satisfaction with the Gojek application among students at FEB, Unjani, while information quality does have an influence on user satisfaction with the Gojek application among students at FEB, Unjani. Simultaneously, both system quality and information quality have an influence on user satisfaction with Gojek among students at FEB, Unjani.